Perilaku Bermasalah Berdasarkan Kondisi Emosional pada Remaja Sekolah Menengah - Defri Yani; Aziz Andreansyah; Risma Anita Puriani (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2026)
High school adolescents are in a vulnerable developmental phase towards emotional and behavioral problems due to rapid biological, cognitive, and social changes. Limitations in emotional management can trigger the emergence of problematic behavior, such as aggressiveness, violations of school rules, conflicts with peers, and bullying, both directly and through digital media. This article aims to analyze problematic behavior in high school adolescents from the perspective of emotional conditions. This study used a qualitative approach with a literature review method of 20 national and international scientific articles obtained through Google Scholar and analyzed descriptively-thematically. The results of the study indicate that adolescent problematic behavior is influenced by the interaction of individual, family, school, and social environment factors that are increasingly complex. Low emotional regulation and emotional intelligence increase the tendency for maladaptive behavior, while family support, a conducive school climate, and Guidance and Counseling services act as protective factors. Therefore, a holistic and sustainable approach is needed through strengthening emotional intelligence, preventive Guidance and Counseling services, and the development of life skills to support the social-emotional development of adolescents.